AGENT-BASED SIMULATION OF DDOS ATTACKS AND DEFENSE MECHANISMS - Kotenko, Igor; Ulanov, Alexander (International Journal of Computing, 2014)
The paper considers an approach to modeling and simulation of cyber-wars in Internet between the teams of software agents. According to this approach, the cybernetic opposition of malefactors and security systems is represented by the interaction of two different teams of software agents – malefactors’ team and defense team. The approach is considered by an example of modeling and simulation of “Distributed Denial of Service” (DDoS) attacks and protection against them. The paper also describes the software environment for multi-agent simulation of defense mechanisms against DDoS attacks developed by the authors and different experiments. The main components of the software environment are outlined. One of the numerous experiments on protection against DDoS attacks is described in detail. The environment developed is based OMNeT++ INET Framework.